A preliminary microscopic and molecular epidemiological survey of endoparasites within wild-caught and UK captive-bred reptiles: Assessing a potential parasitic disease public health risk? - Shea Murray; Lucas J. Cunningham; Paul Rowley; Edouard Crittenden; Nicholas R. Casewell; E. James LaCourse; J. Russell Stothard; Alexandra Juhász (International Journal for Parasitology: Parasites and Wildlife)
In the UK, exotic reptiles are increasingly popular as pets, and housed in zoological collections, whilst venomous snakes of medical importance have long been the focus of herpetological studies. As all reptiles can harbour protist and helminth parasites, some of these may carry tangible zoonotic risk. This study utilised traditional and molecular diagnostic techniques, including sedimentation-flotation, real-time polymerase chain reaction (rtPCR), and necropsy, to investigate endoparasite infections in captive-bred (CB) and wild-caught (WC) reptiles. Representative animals originated from pet shops, zoological and private collections as well as those housed in research herpetariums. Parasitic infections were detected in 21.1% (n = 109) of samples from 58 reptile species across 12 families. The most prevalent infections included nematodes (17.4%), cestodes (0.9%) and protists (3.7%). The nematodes, particularly strongylid (9.3%) and ascarid (5.6%) species, being the most common. Of particular interest, zoonotic genera, Ophidascaris and Giardia were identified. When possible, necropsy revealed latent infections, including prepatent stages of the hookworm Kalicephalus sp. and pentastomid larvae in Echis ocellatus snakes. These accounted for 55.6% of all parasitic infections. Real-time-PCR methods detected additional co-infection overlooked by microscopy, whilst necropsy provided additional insights. These findings highlight the need in the UK for better parasitic screening protocols to enhance captive reptile welfare, mitigate zoonotic risks and safeguard public health.